Pengelolaan Kawasan Industri Berwawasan Lingkungan Di Kota Dumai - Setiawan S, Rizky (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2020)
Dumai City in playing its role in the future has five strategic industrial areas, namely the Dumai Industrial Area (KID) in Pelintung, Lubuk Gaung Industrial Area, Dock Yard Industrial Area, Bukit Kapur Industrial Area and an Industrial Estate in Bukit Timah. Industrial estate development is one of the means to develop an environmentally friendly industry and provide convenience and attractiveness to invest. This is in line with the mandate in Law Number 5 of 1984 concerning Industry that efforts to encourage industrial development need to be carried out through the construction of industrial locations, namely in the form of Industrial Estates. In order to accelerate the development of industrial estates referred to, the government has issued Government Regulation Number 24 of 2009 concerning Industrial Estates, in which every new industrial company after the enactment of this Government Regulation is obliged to enter Industrial Estates. The basis for consideration requires new industries to enter industrial estates so that the industries built are in the right and correct spatial layout, environmentally friendly, effective and efficient management and facilitate the planning and procurement of the necessary infrastructure. Eco-Industrial Park / Estate is a group of industry and service businesses located in a place where the actors in it jointly improve their environmental, economic and social performance through cooperation in managing environmental and resource issues.